Impact of EDDS Dosage on Lead Phytoextraction in Contaminated Urban Residential Soils - Zhang, Zhiming; Sarkar, Dibyendu; Sidhu, Virinder; Warke, Manas; Datta, Rupali (Frontiers in Sustainable Cities, 2022)
Lead (Pb) contamination in soils of residential properties due to peeling and chipping of Pb-based paint can cause human health problems. Phytoextraction is a green technology that has the potential to remediate soil Pb. The efficiency of phytoextraction is dependent on the geochemical forms of Pb in soil. A biodegradable chelating agent, ethylenediaminedisuccinic acid (EDDS), was previously shown to enhance Pb removal by facilitating phytoextraction. In this study, EDDS was tested at various concentrations for its potential in mobilizing Pb in urban residential soils in Jersey City, New Jersey, and San Antonio, Texas. Results show that the concentrations of plant-available forms of Pb increased with the increasing dosage of EDDS from 2 to 30 mmol/L. The addition of EDDS at 30 mmol/L resulted in the conversion of up to 61.2% and 68.9% of the total Pb to plant-available forms in Jersey City and San Antonio soils, respectively. Further analysis showed that, after EDDS application, carbonate-bound Pb, oxide-bound Pb, organic-bound Pb, and residual silicate-bound Pb were transformed to plant-available forms. Higher doses of EDDS performed better than lower doses in transforming soil Pb forms, especially for the oxide-bound Pb. Strong correlations between Pb concentrations measured on-site using a portable X-ray Fluorescence Analyzer (p-XRF) and those obtained in the laboratory using ICP-OES confirmed that p-XRF is a reliable rapid, convenient technology to measure Pb levels in situ.